1999
DOI: 10.1007/s004360050598
|View full text |Cite
|
Sign up to set email alerts
|

Vismione H and structurally related anthranoid compounds of natural and synthetic origin as promising drugs against the human malaria parasite Plasmodium falciparum : structure-activity relationships

Abstract: Natural and synthetic anthranoid compounds were subjected to an evaluation against asexual erythrocytic stages of the human malaria parasite Plasmodium falciparum in vitro. Stimulated by the good activities of Vismia guineënsis extracts, a more detailed investigation of the active principles revealed the pre-nylated preanthraquinone vismione H (1) to be a potent antimalarial [50% growth-inhibitory concentration (IC50) 0.088 microg/ml]. On the basis of this finding a series of chemically related phlegmacins (2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
35
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 25 publications
2
35
0
1
Order By: Relevance
“…0.23 mM. From these prior results, it appears that multiple prenylations are not the only requirements for strong anti-plasmodial activity, as was demonstrated by the potency of Vismione H. 25) The two triterpenoids (6, 7) evaluated in this work displayed moderate activities (IC 50 s of 7.7 mM and 5.1 mM respectively). Betulinic acid has already been evaluated for antiplasmodial activity in a previous work.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…0.23 mM. From these prior results, it appears that multiple prenylations are not the only requirements for strong anti-plasmodial activity, as was demonstrated by the potency of Vismione H. 25) The two triterpenoids (6, 7) evaluated in this work displayed moderate activities (IC 50 s of 7.7 mM and 5.1 mM respectively). Betulinic acid has already been evaluated for antiplasmodial activity in a previous work.…”
supporting
confidence: 54%
“…25) Of note, Vismione H isolated from Vismia guineensis was found to be very active in vitro against P. falciparum (NF 54, clone A1A9), with an IC 50 of ca. 0.23 mM.…”
mentioning
confidence: 99%
“…A literature study of these species revealed that only seven species, Alstonia bonei (Gandhi and Vinayak, 1990;Wright et al, 1993), Abrus precatorius (Limmatvapirat et al, 2004), Cassia occidentalis (Addae- Kyereme et al, 2001;Gasquet et al, 1993;Tona et al, 1999;Tona et al, 2001), Momordica charantia (Amorim et al, 1991;Munoz et al, 2000;Ueno et al, 1996), Nauclea latifolia (Azas et al, 2002;Benoit-Vical et al, 1998), Vernonia colorata (Benoit et al, 1996) and Vismia guineensis (Francois et al, 1999), had previously been investigated for antiplasmodial activity. To our knowledge, this is the first time that Annona muricata, Cola caricaefolia, Canna indica, Desmodium adscendens, Erigeron floribundus, Hoslundia opposita, Mitragyna ciliata, Olax subscorpioidea, Parkia biglobosa, Parketina nigrescens and Uvaria afzelii are being assessed for their antiplasmodial properties.…”
Section: Resultsmentioning
confidence: 97%
“…Several prenylated anthranoids have also been reported with respect to their anti-plasmodial activity. 26) The isolated anthranoids are derivatives of emodin 13. Compounds 5, 6, and 10 with anthracene-9,10-dione skeleton were less active than the anthrones 2, 4 or bianthrones 1 and 12.…”
mentioning
confidence: 99%